Penggunaan Blanko Akta Pejabat Pembuat Akta Tanah Dengan Diterbitkannya Peraturan Kepala Badan Pertanahan Nasional Nomor 8 Tahun 2012 - Swandewi,SH, Ni Luh Putu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 1 (2016)DO - 10.24843/AC.2016.v01.i01.p04, 2016)
One action of realizing the objective of the enactment of the Basic Agrarian Law is the implementation of land registration by using a Land Deed Official certificates as proof of registration of land. The existence of the certificate forms of the Land Deed Official regulated by the Regulation of the Head of National Land Agency Number 3 of 1997 which was then amended by the Regulation of the Head of National Land Agency Number 8 of 2012, both of them regulate about the Land Deed Official certificate using the land certificate forms. The legal consequences of the abovementioned fact raises questions of the followings: What is the legal standing of the land certificate forms issued by a Land Deed Official under the Regulation of the Head of National Land Agency Number 3 of 1997 which has been used by a Land Deed Official as an evidence of transfer of registration of land rights in the Land Affairs Office after the date of March 31, 2013 by the enactment of the Regulation of the Head of National Land Agency Number 8 of 2012 and what efforts should be taken by the Land Deed Officials in the event that the certificate forms of the Land Deed Official issued under the Regulation of the Head of National Land Agency Number 3 of 1997 is not acceptable as an evidence of transfer of registration of land rights after the enactment of the Regulation of the Head of National Land Agency Number 8 of 2012. The study is an empirical legal research, examining the gap between the theories (das solen) with the practices (das sein) in which in the Head of National Land Agency Regulation Number 8 of 2012 Article II point 1 letter a, stipulates that a land certificate form of the National Land Agency (BPN) can still be used. Whereas, in the letter b states that the land certificate forms of the National Land Agency which are no longer being used, shall be returned. In practice, in the Land Deed Official office, the use of a land certificate form of the Land Deed Official issued under the Regulation of the Head of National Land Agency Number 3 of 1997 cannot be accepted in the Agrarian Office. The data and the data sources of this empirical legal research are primary, secondary and tertiary data. The findings of the study indicate the legal standing of the certificate forms of the Land Deed Official issued under the Regulation of the Head of National Land Agency Number 3 of 1997 after the date of 31 March 2013 by law (de jure) is no longer considered as the certificate of the Land Deed Official, but as the evidence of the legal acts set forth therein as the perfect evidence. On the other hand, in practice, the certificate cannot be used as registration evidence by the Agrarian Office, and the solution is to summon the parties to re-sign.
Keywords: blank land deed, Land Deed Official, land registration